2020
DOI: 10.1002/biot.202000231
|View full text |Cite
|
Sign up to set email alerts
|

Humanization of Chicken‐Derived scFv Using Yeast Surface Display and NGS Data Mining

Abstract: Generation of high‐affinity monoclonal antibodies by immunization of chickens is a valuable strategy, particularly for obtaining antibodies directed against epitopes that are conserved in mammals. A generic procedure is established for the humanization of chicken‐derived antibodies. To this end, high‐affinity binders of the epidermal growth factor receptor extracellular domain are isolated from immunized chickens using yeast surface display. Complementarity determining regions (CDRs) of two high‐affinity binde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
(69 reference statements)
0
17
0
1
Order By: Relevance
“…For therapeutic usage, avian-derived antibodies are unsuitable due to their high immunogenicity, likely resulting in anti-drug-antibodies (ADA), which diminish the effectiveness of therapeutic mAbs ( 62 ). To circumvent this problem, our group previously established a YSD-based humanization strategy ( 55 ). In brief, the CDRs of the chicken-derived antibody are grafted onto a human acceptor framework with simultaneous randomization of Vernier residues, critical for CDR orientation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For therapeutic usage, avian-derived antibodies are unsuitable due to their high immunogenicity, likely resulting in anti-drug-antibodies (ADA), which diminish the effectiveness of therapeutic mAbs ( 62 ). To circumvent this problem, our group previously established a YSD-based humanization strategy ( 55 ). In brief, the CDRs of the chicken-derived antibody are grafted onto a human acceptor framework with simultaneous randomization of Vernier residues, critical for CDR orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Our group previously showed that chicken-derived immune libraries, exhibiting common light chains can successfully be screened to isolate high affine binders targeting a large epitope space (53) and that these cLC mAbs can be utilized to construct biparatopic/bispecific antibodies exhibiting improved properties compared to their parental, monospecific counterparts (54). As those molecules were still of avian germline origin, we established an expeditious humanization technique, based on CDR-grafting and randomization of Vernier residues, to generate humanized antibodies with parental-like properties, high germline identity and low number of T cell epitopes (55). This strategy was used here for the first time to generate humanized bi-and trispecific molecules starting from avian antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44% homology to the avian H2 VL domain (data not shown), a pairing with a chicken-derived VH would most probably not result in a functional antibody. Our group recently demonstrated a fast and straightforward solution to humanize avian-derived antibodies via CDR loop transplantation onto human scaffolds, randomization of key residues that dictate loop orientation followed by functional screening using yeast surface display (55). Experiments leading to humanized bispecific and biparatopic chicken-derived antibodies are currently in progress.…”
Section: Discussionmentioning
confidence: 99%